2022
DOI: 10.1136/bmjophth-2022-001149
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of symptomatic dry eye among undergraduate students in Hawassa University College of Medicine and Health Sciences, Hawassa, Ethiopia

Abstract: ObjectiveThis study aimed to assess the prevalence and associated factors of symptomatic dry eye (SDE) among undergraduate students at the College of Medicine and Health Science, Hawassa University, Ethiopia.Methods and analysisInstitution-based cross-sectional study was conducted using a systematic random sampling technique. A total of 311 undergraduate students were recruited to execute the study. Ethical clearance was obtained from the ethical review committee of the school of Medicine and Health Science. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…5 Evidence has shown that the increasing number of diabetic patients worldwide is one of the contributing factors to increase the prevalence of symptomatic dry eye, 6 and the prevalence of dry eye disease in diabetics ranges from 20.6% to 54.3%. [7][8][9][10] In Ethiopia, the prevalence of symptomatic dry eye was 50.5% on postgraduate students in University of Gondar, 11 49.5% on undergraduate students in Hawassa University 12 and 43% on Glaucoma patients in Menelik II tertiary hospital. 13 Although the prevalence of diabetes mellitus in Ethiopia was 6.5%, 14 there was no study that showed the prevalence of symptomatic dry eye among diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…5 Evidence has shown that the increasing number of diabetic patients worldwide is one of the contributing factors to increase the prevalence of symptomatic dry eye, 6 and the prevalence of dry eye disease in diabetics ranges from 20.6% to 54.3%. [7][8][9][10] In Ethiopia, the prevalence of symptomatic dry eye was 50.5% on postgraduate students in University of Gondar, 11 49.5% on undergraduate students in Hawassa University 12 and 43% on Glaucoma patients in Menelik II tertiary hospital. 13 Although the prevalence of diabetes mellitus in Ethiopia was 6.5%, 14 there was no study that showed the prevalence of symptomatic dry eye among diabetic patients.…”
Section: Introductionmentioning
confidence: 99%